2009
DOI: 10.1016/j.otohns.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Test‐retest reliability of drug‐induced sleep endoscopy

Abstract: Objective To determine the test-retest reliability of drug-induced sleep endoscopy (DISE). Methods Prospective cohort study. Patients with OSA underwent two separate DISE examinations. The following outcomes were measured: a global assessment of obstruction at the palate and/or hypopharynx; the degree of obstruction at the palate and hypopharynx; and contribution of individual structures (palate, tonsils, tongue, epiglottis, and lateral pharyngeal walls) to obstruction. Results 32 patients underwent two se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
158
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 23 publications
6
158
1
6
Order By: Relevance
“…Clinically and statistically significant differences were observed in complete and partial concentric collapses, especially at the level of the velum, and partial collapse at the level of the oropharynx, tongue, and epiglottis. In previous studies, Capasso et al [18] and Yoon et al [10] observed important findings in terms of modified anatomic structures in velum, tongue, and epiglottis, but not such significant changes in the oropharynx, which is consistent with our own findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Clinically and statistically significant differences were observed in complete and partial concentric collapses, especially at the level of the velum, and partial collapse at the level of the oropharynx, tongue, and epiglottis. In previous studies, Capasso et al [18] and Yoon et al [10] observed important findings in terms of modified anatomic structures in velum, tongue, and epiglottis, but not such significant changes in the oropharynx, which is consistent with our own findings.…”
Section: Discussionsupporting
confidence: 93%
“…OSA evaluation requires extensive physical examination, imaging, and procedures such as awake endoscopy and DISE [10]. According to American and European literature, DISE is mainly indicated for: 1) moderate and severe OSA patients without morbid obesity who cannot tolerate CPAP as a diagnostic test before indication for surgery or mandibular advancement device; 2) patients with mild OSA or simple snoring with an indication for surgery or mandibular advancement device; and 3) patients with OSA who do not respond to surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…22,23,34,35 Recent studies that address the test-retest and the intra-and interobserver variability in DISE scoring indicate that the reliability of both are moderate to fair, and that inter-observer agreement is higher in ENT surgeons who are experienced with DISE. [36][37][38][39] The limitations of this study also include the fact that DISE was performed only in the supine position, whereas upper airway collapse patterns should ideally be assessed in both the supine and non-supine position 40 . It is well known that the probability of a multilevel collapse is significantly associated with the severity of OSA, as higher AHI values are correlated with a higher percentage of multilevel collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Bruno et al [45] prospectively studied 32 patients undergoing 2 separate DISE examinations. Both examinations were evaluated by one unblinded surgeon and one blinded surgeon (with only knowledge of whether or not the patient had undergone prior tonsillectomy).…”
Section: Dise: Interrater and Test-retest Reliabilitymentioning
confidence: 99%